'Return to Origin Is Non-Existence': Al-Mada'in and Perceptions of Ruins in Abbasid Iraq. (1st July 2017) - Johnson, Sarah Cresap
By looking at early Abbasid writers in ninth- and tenth-century Iraq, this article will analyse the way in which the physical presence but implied immateriality of ruins has contributed to identity formation in the early Islamic period. Since the pre-Islamic period, inspiration in Arabic poetry has stemmed from the visualization of ruins. Abbasid writers treated ruins with an uncertain reverence, at once fearing their implications and admiring their abandoned beauty. Ruins have largely been dismissed as toponyms rather than material spaces in Abbasid writing and poetry. This article attempts to show the connections between the writers' visualizations of physical ruins and their literary manifestations. In Abbasid Iraq, ruins sat in close proximity to but on the periphery of new Islamic cities. This is especially true in the case of the pre-Islamic ruins of al-Mada'in, which were located close to Baghdad. The distant presence of the ruins allowed for them to be revered almost as a shrine within the literary discourse, but also to be feared as a sign of decadence and of inevitable decay.